Brief Preoperative Screening for Frailty and Cognitive Impairment Predicts Delirium after Spine Surgery. (December 2020) - Susano, Maria J.; Grasfield, Rachel H.; Friese, Matthew; Rosner, Bernard; Crosby, Gregory; Bader, Angela M.; Kang, James D.; Smith, Timothy R.; Lu, Yi; Groff, Michael W.; Chi, John H.; Grodstein, Francine; et al.
Abstract : Background: Frailty and cognitive impairment are associated with postoperative delirium, but are rarely assessed preoperatively. The study was designed to test the hypothesis that preoperative screening for frailty or cognitive impairment identifies patients at risk for postoperative delirium (primary outcome). Methods: In this prospective cohort study, the authors administered frailty and cognitive screening instruments to 229 patients greater than or equal to 70 yr old presenting for elective spine surgery. Screening for frailty (five-item FRAIL scale [measuring fatigue, resistance, ambulation, illness, and weight loss]) and cognition (Mini-Cog, Animal Verbal Fluency) were performed at the time of the preoperative evaluation. Demographic data, perioperative variables, and postoperative outcomes were gathered. Delirium was the primary outcome detected by either the Confusion Assessment Method, assessed daily from postoperative day 1 to 3 or until discharge, if patient was discharged sooner, or comprehensive chart review. Secondary outcomes were all other-cause complications, discharge not to home, and hospital length of stay. Results: The cohort was 75 [73 to 79 yr] years of age, 124 of 219 (57%) were male. Many scored positive for prefrailty (117 of 218; 54%), frailty (53 of 218; 24%), and cognitive impairment (50 to 82 of 219; 23 to 37%). Fifty-five patients (25%) developed delirium postoperatively. On multivariable analysis, frailty (scores 3 to 5 [odds ratio, 6.6; 95% CI, 1.96 to 21.9; P = 0.002]) versus robust (score 0) on the FRAIL scale, lower animal fluency scores (odds ratio, 1.08; 95% CI, 1.01 to 1.51; P = 0.036) for each point decrease in the number of animals named, and more invasive surgical procedures (odds ratio, 2.69; 95% CI, 1.31 to 5.50; P = 0.007) versus less invasive procedures were associated with postoperative delirium. Conclusions: Screening for frailty and cognitive impairment preoperatively using the FRAIL scale and the Animal Verbal Fluency test in older elective spine surgery patients identifies those at high risk for the development of postoperative delirium. Abstract : Screening for frailty and cognitive impairment preoperatively using the brief FRAIL (measuring fatigue, resistance, ambulation, illness, and weight loss) scale and the Animal Verbal Fluency test in older elective spine surgery patients identifies those at high risk for the development of postoperative delirium.Supplemental Digital Content is available in the text.